Keyboard controller VGA controller online - Mohamad Sharif, Abu Bakar (2010)
This project describes about the design of VGA (Video Graphic Array) Controller and PS-2 keyboard controller using combination of three bit input data to control eight differences colours to display text at monitor by using keyboard as database online for the input. Three colour signal referred to collectively as R (red), G (green) and B (blue) signal. The VGA monitor using resolution of 640 by 480 by mode to display colours. The project constructed by using Xilinx ISE 10.1 software and Xilinx Spartan-3E board to develop the project into a complete module. The project using the Finite State Machine (FSM) technique to generate HDL coding based on the VGA timing diagram specification. To get VGA monitor controller properly, the timing diagram must be correctly. The design will be written using VHDL (VHSIC Hardware Description Language) coding style based on FSM to ensure the VGA controller and PS-2 controller work properly. The behavioral simulation was done by using Xilinx ISE Tool software to verify the functionality of the design. The Spartan 3E starter Kit board was chosen to implement the design